(untitled) (Research, Society and Development, 2023)
Objective: In this study, we analyzed the benefit of using CPAP in a Young, obese individual with Tourette’s syndrome and obstructive sleep apnea-hypopnea syndrome. Method: This is a case study with a quantitative approach. The participant underwent a nightly polysomnographic examination pre-test and post-test of CPAP application with an average of more than 6 hours per night in 21 days of evaluation. Completed data in a form, created by the authors, which contains general data, Epworth sleepiness scale, and tics scale (YGTSS), and polysomnographic data. The study is approved by the Research Ethics Committee. The results show significant relevance in terms of progress in improving sleep architecture, reducing respiratory events and awakenings, improving alertness scored by the Epworth scale. Conclusions: Further, the results suggest and point out the benefits and the possibility of using nocturnal CPAP as a therapeutic in sleep efficiency for patients diagnosed with Tourette’s syndrome and sleep apnea-hypopnea syndrome.